STRATEGI BRANDING (MEREK) SEBAGAI UPAYA PENGEMBANGAN PRODUK KREATIF USAHA MIKRO KECIL MENENGAH (UMKM) CEMILAN KAMPOENG BAJA DI RW 11 KELURAHAN CISARUA KECAMATAN CIKOLE KOTA SUKABUMI JAWA BARAT - Adhistiany Sopyan, Dhea; Nurul Afiya, Rosita; Sri Hanifah, Sani; Ayu Sagita, Siti; Zulfani, Syifa (LPPM Politeknik Pajajaran ICB Bandung, 2022)
In a Student Work Lecture (KKM) activity there is the Tri Dharma of Higher Education in which there are three aspects, namely education, research and service which in these three aspects where the third point is community service has been carried out by students. Our group carries out KKM activities and conducts research on branding strategies as an effort to develop creative products for micro, small and medium enterprises (MSMEs) of Kampoeng Baja snacks in RW 11, Cisarua Village, Cikole District, Sukabumi City, West Java Province. The purpose of this study aims to analyze the influence factors of how important branding is to a product, this becomes a reference for how much the product can be accepted in society so that it produces a symbiosis of mutualism or things that are mutually beneficial both for consumers and than product creators or often called a company. . The research method used in the current research is qualitative, technically using observation techniques in general and thoroughly, meaning starting from interviews, persuasive interactions and outreach about the importance of branding in a product where you can say this branding is the spearhead of a product that is produced. company. The results of this study state that periodic application can affect marketability as a form of product acceptance in the hands of the public.